Real exchange rate, current account and capital accumulation in an intertemporal optimizing model of a small open economy - Brito, Paulo (2021)
This paper deals with the long run consequences of productivity and rate of time preferences changes on a small open economy with an empphasis ipon the dynamics of consumption, physical capital, the current account an the real exchange rate. The economic structure and the questions to be answered are the same as in the FEREX (fundamental equilibrium real exchange rate) model of ALLEN (1989) and STEIN (1989) However, in the contrast with these studies, the main macroeconomic functions are derived from an explicit enunciation and solution of the (continuous time) intertemporal optimization problems assumed to be the foundations of the behavioral functions attributable to the main representative agents, in a context of perfect foresight.